Distributed Mobility Management in 6LoWPAN-Based Wireless Sensor Networks - Moneeb Gohar (International Journal of Distributed Sensor Networks, 2015)
In 6LoWPAN networks, several mobility management schemes have been proposed based on Mobile IPv6 (MIPv6) and Proxy Mobile IPv6 (PMIPv6). However, the existing schemes are centralized, and thus they have many serious drawbacks such as nonoptimal data route, injection of unwanted data traffics into core networks, increased cost of network engineering, and large registration and handover delays. To overcome these limitations, we propose new distributed mobility management schemes for 6LoWPAN networks. In the proposed schemes, Home Agent (HA), Local Mobility Anchor (LMA), and Mobile Access Gateway (MAG) functions are implemented in 6LoWPAN gateways, and the handover operations are performed directly between two neighboring 6LoWPAN gateways. By numerical analysis, we show that the proposed distributed schemes can significantly reduce the registration and handover delays, compared to the existing centralized mobility schemes.